Reforestation and Carbon Sequestration: Opportunities for Regional Climate Mitigation - Kumar, Anil; Kelkar, Dr. Gautam Dashrath; Kar, Dr. Biswabandita; Dixit, Dr. Pravat Ranjan; Godboley, Buddharatna J. (International Journal of Aquatic Research and Environmental Studies, 2026)
Planting trees is being seen more and more as one way that nature can be harnessed to lower CO2 concentrations within the atmosphere by rehabilitating degraded areas. Nevertheless, regional differences in available land, land productivity, and land use play a role in the potential impact of such efforts on the environment. This study evaluated regional reforestation opportunities and associated carbon sequestration potential across the United States, with emphasis on county-level patterns, land-use contributions, and ecoregional variation. A quantitative cross-sectional design was applied using county-level and ecoregional reforestation opportunity data. The final analytical dataset included 3,109 county observations. Descriptive statistics, Pearson correlation analysis, ordinary least squares regression, land-use contribution analysis, state-level aggregation, county hotspot identification, and ecoregional comparison were conducted using Python. The reforestation opportunity area showed a strong positive association with carbon sequestration potential (r = 0.848), and regression analysis explained 71.8% of the variation in sequestration potential. Texas recorded the highest total state level sequestration potential, while Oregon and California contained major county-level hotspots. Pasturelands contributed the largest share of total carbon sequestration potential, followed by shrub and grass systems. Ecoregional analysis identified Southeast U.S. conifer savannas, Appalachian Piedmont forests, and Piney Woods as leading ecological regions for reforestation-based mitigation. Reforestation will be able to make significant contributions towards regional climate mitigation, provided that its planning is based on factors such as land availability, ability to store carbon dioxide, suitability for land use, and ecological conditions.